The Relationship among Supervision, Integrity, and Performance of Primary School Teachers - Siti Rahmah; Gimin Gimin; Afrianto Afrianto (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2021)
This study aims to analyze the relationship between supervision, integrity and performance of primary school teachers. The participantes of the study were 150 teachers of public elementary schools in Dumai Barat subdistrict, Dumai city, and the sample was determined using the proposite stratifield random sampling technique. The method of data collection was done by distributing questionnaires for the supervision and integrity variables, while for the teacher performance variable it was with documentation. The results of the study show that there is a positive correlation between supervision on teacher performance, a positive correlation between integrity and teacher performance, and a positive correlation between supervision, integrity and teacher performance.This study concludes that there is a positive and significant correlation among supervision, integrity, and performance of primary school teachers in Dumai Barat Subdistrict, Dumai City.